1995
DOI: 10.1017/s0025315400015204
|View full text |Cite
|
Sign up to set email alerts
|

Tracking of Blue Lights by Hyperiid Amphipods

Abstract: INTRODUCTIONThe problems of observing the behaviour of mid-water animals are considerable. The depths involved are generally too great to allow free diving, and because the population density is low, useful observations from submersibles and remote cameras are rare. Animals brought to the surface are often in too poor a condition to behave at all normally. The hyperiid amphipods are one of the best groups to work with in trying to overcome these difficulties. They are relatively common and frequently observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…The visual sys tem of this species, however, is not especially sensitive to those wavelengths (Cohen & Frank 2007), and the function of the luminescence is not known. Nonluminous amphipods will track blue light sources (Land et al 1995), and it is suggested that they use this in hunting for the biolu minescent jellies they parasitize. Although the group that includes Scina and Proscina is not usually thought to be parasitic, examples of associations between Proscina and gelatinous hosts have been found (Gasca et al 2007).…”
Section: Crustaceansmentioning
confidence: 99%
“…The visual sys tem of this species, however, is not especially sensitive to those wavelengths (Cohen & Frank 2007), and the function of the luminescence is not known. Nonluminous amphipods will track blue light sources (Land et al 1995), and it is suggested that they use this in hunting for the biolu minescent jellies they parasitize. Although the group that includes Scina and Proscina is not usually thought to be parasitic, examples of associations between Proscina and gelatinous hosts have been found (Gasca et al 2007).…”
Section: Crustaceansmentioning
confidence: 99%
“…Bioluminescence in most marine bacteria peaks at the wavelength of ∼490 nm (25), which, not surprisingly, is near the wavelength least absorbed in seawater (26). Several zooplankton taxa [e.g., two species of the copepod Pleuromamma (27), hyperiid amphipods (28), and some deep-sea crustaceans (29)] were shown to be sensitive to similar wavelengths. Mesopelagic crustaceans have a single peak of spectral sensitivity at 470-500 nm, presumably exhibiting greater sensitivity to bioluminescence than to downwelling light (30).…”
Section: Discussionmentioning
confidence: 99%
“…Although less intensively documented than fishes, crustacean (copepods, amphipods, isopods…) visual system is also reported to have sensitivity shift to bluer wavelength, which aids their bioluminescence detection (Cohen and Forward, 2002;Frank et al, 2012;Marshall et al, 1999;Nishida et al, 2002). In laboratory experiments, Land et al (1995) demonstrated that amphipods where attracted to a blue-light-emitting diode. Unfortunately, and despite these statements, rare studies have investigated the effect of bioluminescence on the ingestion rates of predators (Figure 1, step 2).…”
Section: How Do Bioluminescent Bacteria Impact the Biological Carbon mentioning
confidence: 99%